Changes In Soil Physical Properties And Crop Productivity As Influenced By Different Tillage Depths And Cropping Patterns (Bangladesh Journal of Agricultural Research, 2013)
A series of field experiments was conducted at BARI central farm to observe the changes in soil densities, moisture retentive properties, and crop productivity as influenced by different tillage depths and cropping patterns. The tillage depth showed significant effect on wheat yield. Grain yield of wheat significantly increased from 2.86 t/ha (minimum tillage depth) to 5.33 t/ha (tillage depth up to 20-25 cm). Tillage depths and cropping patterns individually and their interaction significantly affected the yield of BRRI dhan32. The highest grain yield of rice (5.82 t/ha) was found in the tillage depth up to 20-25 cm under wheat-dhaincha-T. aman cropping pattern, whereas the lowest yield (2.08 t/ha) was found in the minimum tillage depth under wheat-fallow-T. aman cropping pattern. Soil densities and soil moisture retentive properties were significantly affected by interaction of tillage depths and cropping patterns. The bulk density and particle density of soil were decreased but the porosity and soil moisture at field capacity and permanent wilting point were increased with the increase of tillage depths. Tillage depth up to 20-25 cm by chisel plough under wheatdhaincha- T. aman cropping pattern conserved more moisture in the soil profile and improved other soil physical properties i.e. reduced the bulk density, increased porosity, increased water holding capacity and available water content of soil, thus maintained an optimum soil water infiltration rate and soil strength. The study revealed that the soil physical properties were significantly improved and crop yield significantly increased under tillage depth up to 20-25 cm by chisel plough under wheat-dhaincha-T. aman cropping pattern. Bangladesh J. Agril. Res. 38(2): 289-299, June 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i2.15891